RANCANG BANGUN TEMPAT SAMPAH OTOMATIS BERBASIS MIKROKONTROLER - Adi Kurniawan, (2022)
Until now trash has become a big problem that causes a dirty environment. People who have the habit of littering have a bad impact on the environment. An innovation for trash bins has appeared that can decrease littering. An innovation for trash bins uses a microcontroller called Arduino. Arduino is a microcontroller that is easy to use for any user. This tool uses an ultrasonic sensor to detect a person nearby and give a signal in sound form if it has been fueled. A servo motor is used as a drive system to open the trash bin. The trash bin will open if someone comes to it less than 30 cm away. Sensor will give a sound signal if the volume of the trash bin is less than 5 cm from the cover trash bin. Production of automatic trash bins starts from study of literature, design programs and electrical, assembly, and test performance tools. A drive system used in this study is simple machine theory. According to the performance test for a response sensor to catch input distance, this tool has an average response of 0,38 seconds, and error under 5 percent.